ANALISIS FAKTOR KEJADIAN PENYAKIT GINJAL KRONIS PADA PASIEN DI RSUP HAJI ADAM MALIK MEDAN - Rini Andarwati; Henny Yusnita (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2026)
According to 2024 data from the Indonesian Ministry of Health, chronic kidney disease is influenced by a number of factors, such as type 2 diabetes, kidney inflammation, the use of pain relievers, a family history of the disease, high blood pressure, abdominal injuries, premature birth, and several other medical conditions. At Haji Adam Malik General Hospital in Medan, the number of patients with chronic kidney disease has increased by 58% over the past two years, from 357 cases in 2022 to 858 cases in 2023. This study aims to examine the factors associated with the onset of chronic kidney disease among patients at this hospital. The research method used was an analytical observational study with a cross-sectional design. The study sample consisted of 50 patients with chronic kidney disease selected using quota sampling. Data analysis was performed using the Chi-square test. The results of the study indicate that factors associated with the incidence of chronic kidney disease include age 41–60 years (58%), male gender (60%), self-employed occupation (26%), high school education level (44%), family history of disease (64%), unhealthy lifestyle (66%), medication use (94%), and the presence of comorbidities (82%). The study’s conclusion confirms that family history of disease, unhealthy lifestyle, medication use, and comorbidities have a significant association with the incidence of chronic kidney disease, with a p-value < 0.05